PENGELOLAAN POTENSI SUMBERDAYA KELAUTAN SEBAGAI UPAYA PENINGKATAN PENDAPATAN NELAYAN (Studi Kasus Community-Based Management Wilayah Pesisir di Kabupaten Tuban) - Shofwan, -; Khusaini, Moh.; Badriyah, Nurul (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2008)
The objectives of this research were to analyze Community-Based Managementapplication, influence and factors to management of coastal resources especiallyincreasing fisherman income on 5 districts in sub-province Tuban. The results showedthere are extensive community participation, capacity building and village coastalmanagement plans. These plans are significant in many ways. Planning is alsounderway to scale-up from pilot sites to a provincial program that provides technicaland financial support services to village government and communities coast-wide.Keywords: Community-Based Management, Coastal Resources, Coastal Village,Fisherman Income